Corneal confocal microscopy reveals trigeminal small sensory fiber neuropathy in amyotrophic lateral sclerosis - Ferrari, Giulio; Grisan, Enrico; Scarpa, Fabio; Fazio, Raffaella; Comola, Mauro; Quattrini, Angelo; Comi, Giancarlo; Rama, Paolo; Riva, Nilo (Frontiers in Aging Neuroscience, 2014)
Although subclinical involvement of sensory neurons in amyotrophic lateral sclerosis (ALS) has been previously demonstrated, corneal small fiber sensory neuropathy has not been reported to-date. We examined a group of sporadic ALS patients with corneal confocal microscopy, a recently developed imaging technique allowing in vivo observation of corneal small sensory fibers. Corneal confocal microscopy examination revealed a reduction of corneal small fiber sensory nerve number and branching in ALS patients. Quantitative analysis demonstrated an increase in tortuosity and reduction in length and fractal dimension of ALS patients’ corneal nerve fibers compared to age-matched controls. Moreover, bulbar function disability scores were significantly related to measures of corneal nerve fibers anatomical damage. Our study demonstrates for the first time a corneal small fiber sensory neuropathy in ALS patients. This finding further suggests a link between sporadic ALS and facial-onset sensory and motor neuronopathy (FOSMN) syndrome, a rare condition characterized by early sensory symptoms (with trigeminal nerve distribution), followed by wasting and weakness of bulbar and upper limb muscles. In addition, the finding supports a model of neurodegeneration in ALS as a focally advancing process.